2020
DOI: 10.3390/nu12123836
|View full text |Cite
|
Sign up to set email alerts
|

General Health, Systemic Diseases and Oral Status in Adult Patients with Coeliac Disease

Abstract: The prevalence of coeliac disease in the general population is 0.5–1%; however, most patients remain undiagnosed until adult age. In some cases, the onset is represented by sub-clinical signs, some of which can be found in the mouth. The aim of this research was to identify any associations between the clinical characteristics of coeliac disease and oral manifestations. A structured questionnaire was administered to a group of 237 individuals with coeliac disease. 100% of the subjects fully completed the quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…In this respect, it has been suggested that adherence to a gluten-free diet leads to an oral microbiota favouring gingival health [10]. In addition, it has been shown that CD patients who do not follow a strict gluten-free diet display more systemic inflammation, which can be related to gingival inflammation [47].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it has been suggested that adherence to a gluten-free diet leads to an oral microbiota favouring gingival health [10]. In addition, it has been shown that CD patients who do not follow a strict gluten-free diet display more systemic inflammation, which can be related to gingival inflammation [47].…”
Section: Discussionmentioning
confidence: 99%
“…A recent pediatric study confirmed that children with CD have a higher rate of recurrent aphthous stomatitis and dental enamel defects than the healthy population [ 151 ]. Moreover, CD is significantly associated with a higher prevalence of caries and dentin sensitivity, while an adequate gluten-free diet controls gingival bleeding [ 152 ].…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, the other seventeen studies [11,[20][21][22][23][24]26,30,31,33,34,36,[39][40][41][42]44] presented data indicating that the occurrence of RAS in the study group was statistically significantly higher when compared to the control group.…”
Section: Recurrent Aphthous Stomatitis (Ras)mentioning
confidence: 99%